Analisis Perubahan Suhu Terhadap Panjang Gelombang Pada Media Fiber Optik Berstruktur Singlemode-Multimode - Muhammad Adi Riswanto; Mochammad Junus; Yoyok Heru Prasetyo Isnomo (Politeknik Negeri Malang, 2020)
The increase in temperature on optical fiber results in an increase in the refractive index and Numerical Aperture, resulting in spread and absorption losses in the optical fiber. So it is considered necessary to discuss the effect of temperature changes on wave length in axially connected Singlemode-Multimode fiber optic media. Optical fiber connected to OSA is heated using a heater to show the wavelength value, before converted into color. Then convert it into CCT so as to produce a temperature value in kelvins. In this study, singlemode, multimode, singlemode-multimode fiber are used. The connection to each optical fiber and light source uses a Fusion Splicer and Visual Fault Locator with a wavelength of 660 nm and 680 nm, respectively. Results show that the higher the temperature, the farther the wavelength shift. The singlemode-multimode cable has the farthest shift value of 8.44 nm at 660 nm and 9.3 nm at 680 nm. Singlemode-multimode cable has the best measurement accuracy value. Because at a wavelength of 660 nm, the difference between the temperature values ??measured on the thermocouple and those calculated on the matlab has an average percentage of 0.54%. Meanwhile, at a wavelength of 680 nm it is 0.63%.